Assessing Students’ Biology Interests and Perceived Teacher Effectiveness in Rural Communities: Implications for Rural Biology Education - Regina Ijeamasi Enebechi (Action Research Journal Indonesia (ARJI), 2026)
Persistent disparities in science outcomes between rural and urban students highlight the need to better understand how students’ interest in Biology and their perceptions of teacher effectiveness interact to shape learning in rural contexts. Maintaining students’ interest in Biology requires a clear understanding of the factors that influence their learning outcomes in the subject. The study employed a cross-sectional survey research design to investigate the relationship between teacher effectiveness and Biology interest among rural students. The sample consisted of 227 secondary school students randomly selected from five community schools in Ezeagu, Enugu State, Nigeria. The results indicated that Subject matter mastery is the only significant predictor of students’ interest in Biology (β = –.315, t = –4.411, p = .000). However, the relationship is negative. Other dimensions of teacher effectiveness did not significantly predict students’ interest (p > 0.05). This implies that these aspects, as perceived by students, do not independently influence their interest levels in Biology. The study therefore concluded that the affective components of teacher effectiveness play a critical role in enhancing rural students’ interest in Biology